Balancing Biodiversity Availability and Needs among the Orang Rimba in Bukit Duabelas National Park, Jambi - Haidir; Yanto Santosa; Arzyana Sunkar; Djuara P. Lubis; Ria Sukma Dewi; Wulandari Mulyani; Saefullah (Postgraduate, University of Mataram, 2026)
Bukit Duabelas National Park is a protected area that functions as both a biodiversity conservation area and a living space for the Orang Rimba community. While previous studies have mainly documented Orang Rimba ethnobiological knowledge, this study quantitatively links biological resource availability, utilization intensity, and sustainability prospects within an indigenous livelihood system. Field observations, vegetation sampling, line transects, and semi-structured interviews were conducted with 88 respondents from 13 tumenggung groups. The data were analyzed using quantitative and qualitative descriptive analysis, and sustainability assessments based on plant regeneration structure and wildlife harvest-to-production ratios. The results showed that the Orang Rimba utilized 74 plant species from 45 families and eight wildlife species for food, medicine, construction, trade, clothing, and cultural purposes. Plant use was dominated by food and medicinal resources, with average harvesting intensities of 245.34 and 203.75 events per year, respectively. A sustainability assessment classified 14.86% of plant species as sustainable, 40.54% as moderately sustainable, and 44.59% as unsustainable. Wildlife use was generally unsustainable because maximum harvest estimates exceeded conservative annual production and upper reproductive estimates for most species. These results stress the need for adaptive and participatory management strategies that prioritize both biodiversity preservation and sustainable Orang Rimba livelihoods.